Intrahousehold valuation, preference heterogeneity, and demand for an agricultural technology in India - Gulati, Kajal; Ward, Patrick S.; Lybbert, Travis J.; Spielman, David J. (2019)
In this paper we examine some of the intrahousehold decisionmaking dynamics that shape household’s decision to adopt a mechanical rice transplanting technology that significantly reduces the demand for labor during transplanting. To study the adoption decision, we consider the willingness-to-pay for MRT services, both at the level of individual men and women within the same households, as well as at the household level. We find that women value MRT more than men, but this difference in valuation is not driven by differences in their individual characteristics, but primarily from differences in preferences. Despite women valuing MRT more than men, they do not significantly influence the household’s technology adoption decision. The intrahousehold differences in valuation disappear when women engage in hired wage work, suggesting that women value MRT in order to potentially reallocate farm labor to other unpaid family work. These results have implications for rural labor market welfare because agricultural and labor productivity gains due to MRT adoption may push women into more traditional gendered labor divisions.